PENGGUNAAN JEJARING SOSIAL TWITTER SEBAGAI MEDIA PROMOSI PADA RESTORAN RANJANG 69: Rosianti Utami Dewi, Zam Zam Nurjaman - Jurnal COMMED (Prodi Ilmu Komunikasi Universitas Putera Batam, 2017)
Internet as a new medium that provides a lot posibility for marketing development. Social media presence allows the owner of the product, brand, traders to interact directly, in time and inexpensively without having to meet directly. Marketers using social media to carry out various marketing activities including promotion. This study aims to determine the use of Social Networking Twitter as a promotional medium in marketing communications of RANJANG 69 restaurants. The research used in this study is a qualitative method with descriptive research. Promotional strategy developed with regard to informing the community that the company utilizes Ranjangers are active followers twitter of account RANJANG 69 to perform various activities post associating with RANJANG 69 to inform about RANJANG 69 product, location, events and others. Persuading aims to educate the advantages of products owned, while reminding made through recalled to forming engagment to consumers by creating sustainable tweets.